pMPES: A Modular Peptide Expression System for the Delivery of Antimicrobial Peptides to the Site of Gastrointestinal Infections Using Probiotics - Kathryn Geldart; Brittany Forkus; Evelyn McChesney; Madeline McCue; Yiannis N. Kaznessis (MDPI AG, 2016)
Antimicrobial peptides are a promising alternative to traditional antibiotics, but their utility is limited by high production costs and poor bioavailability proﬁles. Bacterial production and delivery of antimicrobial peptides (AMPs) directly at the site of infection may offer a path for effective therapeutic application. In this study, we have developed a vector that can be used for the production and secretion of seven antimicrobial peptides from both Escherichia coli MC1061 F' and probiotic E.coli Nissle 1917. The vector pMPES (Modular Peptide Expression System) employs the Microcin V (MccV) secretion system and a powerful synthetic promoter to drive AMP production. Herein, we demonstrate the capacity of pMPES to produce inhibitory levels of MccV, Microcin L (MccL), Microcin N (McnN), Enterocin A (EntA), Enterocin P (EntP), Hiracin JM79 (HirJM79) and Enterocin B (EntB). To our knowledge, this is the ﬁrst demonstration of such a broadly-applicable secretion system for AMP production. This type of modular expression system could expedite the development of sorely needed antimicrobial technologies